Sepsis and Septic Shock in Pregnancy - Islamy, Nurul; Aziz, M. Alamsyah; Yonata, Ade; Lumentut, Anastasia M.; Maelissa, Merlin M.; Khaerunnisa P, Maya; Wirawan, Wahyudi (Journal La Medihealtico, 2025)
Sepsis during pregnancy is a critical condition that leads to organ dysfunction due to an abnormal response to infection. It remains a significant cause of maternal morbidity and mortality worldwide. The World Health Organization (WHO) reports a global prevalence of 4.4% of live births affected by maternal sepsis, with varying incidences across countries. Sepsis ranks among the top five causes of maternal deaths globally, contributing to 12.7% of pregnancy-related mortality in the United States. The physiological changes during pregnancy, such as increased blood volume and immune response modulation, create conditions that make pregnant individuals more susceptible to infections, complicating the timely diagnosis of sepsis. Due to these physiological differences, common sepsis screening tools like qSOFA and SOFA are often inadequate in pregnant patients, highlighting the need for specialized diagnostic and management strategies. Early detection and timely treatment are essential to improving maternal outcomes. Several screening tools, such as the Maternal Early Warning Trigger (MEWT) tool, have been designed to aid in the early identification of deteriorating maternal health. Once sepsis is suspected, prompt antibiotic therapy, fluid resuscitation, and vasopressor support are critical to prevent progression to septic shock. Additionally, controlling the infection source through surgical intervention or drainage may be necessary. Despite advances in sepsis management, challenges remain, particularly in identifying and treating sepsis in pregnant patients due to overlapping symptoms with normal pregnancy changes. Therefore, early recognition and appropriate intervention are key to reducing the impact of sepsis during pregnancy.